IMPLEMENTASI KEBIJAKAN PENDIDIKAN GRATIS DI SMPN 35 BERASRAMA KAUR - Reni Zulaikha (UNIVERSITAS BENGKULU, 2022)
In general, this study aims to describe the implementation of the free education policy in Public Junior High Schools 35 Boarding School Kaur Regency. In particular, this study aims to described : 1) the content of the free education policy at the school; 2) implementation of the free education policy at the school; 3) obstacles faced in implementing the free education policy at the school ;4) efforts of the education office in overcoming obstacles to free education policy at the school. The research method used is a policy study, using a qualitative method approach. There were three data collection techniques used in this study, namely: interviews, documentation and observation. Analysis technique used was inductive with steps: reduction of data, data display, data comparison and conclusion criteria. The result of the research showed the implementation of the free education policy at the state Public Junior High School 35 Boarding School Kaur that school don’t pay any money. Suggestions research: the government should be more serious in paying attention to free education specially at the state Public Junior High School 35 Boarding School Kaur